Pengaruh Literasi Keuangan, Pendapatan, Risiko Investasi, dan Fluktuasi Harga Emas terhadap Minat Berinvestasi Emas Nasabah Bank Syariah Indonesia Cabang Balikpapan - Muhammad Sayid Abdullah Ali; Rihfenti Ernayani; Ita Yuni Kartika (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
The research aims to identify the influence of financial literacy, income, investment risk, and gold price fluctuations on customers’ interest in gold investment at Bank Syariah Indonesia Balikpapan Branch. The research was conducted at Bank Syariah Indonesia Balikpapan Branch. The research uses primary data types with data collection techniques through the distribution of questionnaires in google form and directly. The sampling method used is the Total Sampling and the sample obtained was 1.200 respondents. The data analysis methods used in the study are Partial Least Square-Structure Equation Model (PLS-SEM) with the smartPLS3.0 application. The results of the study show that financial literacy, investment risk, and gold price fluctuations each affects the customers’ interest in gold investment at Bank Syariah Indonesia Balikpapan Branch. However, income does not affect the customers’ interest in gold investment at Bank Syariah Indonesia Balikpapan Branch.